A new species of the genus Oreonectes (Cypriniformes: Nemacheilidae) from Guizhou, China - Deng, Huaiqing; Xiao, Ning; Hou, Xiufa; Zhou, Jiang (Zootaxa, 2016)
This study examined the morphological and phylogenetic characteristics of Oreonectes shuilongensis sp. nov. The genus Oreonectes is distributed only in southwestern China and northern Vietnam.  Sixteen specimens of cavefish were captured in the Shuilong Township in Guizhou Province of China and identified as a new species of Oreonectes (Cypriniformes: Nemacheilidae).  Maximum likelihood was used to construct phylogenetic trees based on data for Nemacheilidae species accessible on GenBank. Molecular phylogenetic analyses showed that O. shuilongensis is closely related to O. platycephalus from which it is distinguished by having 6 vs. 5 branched anal rays, ratio of body length to body height 7.0–7.9 vs. 5.6–7.0, ratio of head length to distance between eyes 3.5–4.9 vs. 2.0–2.4, naked vs. scaly body, densely distributed fine black stains except on abdomen, and semitransparent body. Oreonectes shuilongensis is the only species of the genus not distributed in Guangxi Province. This study has contributed to the overall knowledge about the distribution of Oreonectes.